The Effectiveness of Acupressure and Common Cold Massage on Healing Cold in Infants - Maftuchah, Maftuchah; Wulaningsih, Indah; Ulfah, Rizqa (JURNAL KEBIDANAN, 2024)
Acute respiratory infection (ARI) is a common disease that affects the community, particularly children and infants. Acute respiratory infections (ARI) that occur in children and infants are very dangerous because they can interfere with eating and sometimes lead to more serious lower respiratory tract infections if not treated properly. Acupressure and common cold massage are non-pharmacological methods of cough and cold treatment. A preliminary study was conducted in the working area of the Balapulang Health Center on September 7, 2021, and a total of 200 babies were obtained. Knowing the effectiveness of acupressure and common cold massage on the duration of cough and cold healing at the Balapulang Public Health Center. A quasi-experimental design with a two group posttest design with a sample size of 20 babies. There is a difference in the effectiveness of acupressure and common cold massage on the duration of cough and cold healing, as indicated by the mean rank values of the acupressure group of 14.05 and the common cold massage group of 6.95. Common cold massage is more effective than acupressure On the healing time of cough and cold in babies with a p-value of 0.005